Masculinity and Spirituality in Victorian Culture - Bradstock, Andrew. author. aut Link
XI, 232 p.
Keywords: In its specially-commissioned fourteen chapters, this important book discusses an impressively wide range of issues around the theme of male spirituality in the nineteenth century, drawing from history, cultural studies, art history and literary criticism. Topics explored include: ideological and iconographical representations of masculinity across the major Christian denominations; militarism and hymnody; male homosexuality and homoeroticism. The book is not afraid to explore controversial areas, nor to go beyond the generally acknowledged 'canon' of prescribers of gender identity: it includes, for example, leading nonconformist figures like William Booth and Charles Haddon Spurgeon, and early gay writers like John Addington Symonds.